Alopecia Areata Associated with Localized Vitiligo - Shankarling D. Kuchabal; D.S. Kuchabal (Karger Publishers, 2010)
Alopecia areata is a common cause of noncicatricial alopecia that occurs in a patchy, confluent or diffuse pattern. It may occur as a single, self-limiting episode or may recur at varying intervals over many years. The association of alopecia areata with localized vitiligo has not been reported. The association of alopecia areata with localized vitiligo in the same patient is documented here; it is the first of its kind.